The 2017 General Election in Scotland: a Return to Multi-party Politics? - Fiona Simpkins (Revue Française de Civilisation Britannique)
Although Scotland had long been a Labour stronghold, devolution soon appeared to have served as a political platform for the nationalists who were able to assert their domination of Scottish politics after they obtained both an overall majority of seats in Holyrood in 2011 and 56 out of 59 Scottish seats at Westminster in 2015. Scotland had become a dominant-party polity and the SNP the third biggest party in Britain. However, the June 2017 general election appears to have seriously dented the SNP’s electoral prospects and has corresponded not only to the unexpected resurgence of Conservatism in Scotland but also to a new surge in Labour votes. It appears evident that the Brexit vote following the European referendum of June 2016, which has dominated the British political debate since then, has had a profound impact on Scottish politics. This paper therefore seeks to examine Scotland’s return to multi-party politics in light of the twin impact of Brexit and the constitutional issue on the 2017 general election results in Scotland.